Antenas de ondas vazadas para redes celulares 5G - Santos, Renan Alves dos (2016)
This work is regarding the development of three innovative antennas applied to the fifth generation of cellular networks 5G. First, the project of a wideband printed antenna with bandwidth from 4.0 to 8.0GHz, gain of 10.5dBi and frequency reconfigurable radiation pattern is presented. Then, a dielectric rod antenna operating from 27.65 to 28.43GHz, gain of 12.2dBi and a quasiomnidirectional radiation pattern is developed. Finally, there is slotted waveguide antenna operating from 27.24 to 28.59GHz and gain of 17.39dBi is reported. The development methodology is based four steps: design and analytical calculations; numerical simulations and optimization; prototypes fabrication; experimental characterization. The ANSYS HFSS was used for carrying out the numerical analysis. The prototypes production and characterization were realized at the WOCA and ICC-Hardware laboratories from Inatel. An excellent agreement between numerical e experimental results was observed for the three proposed antennas.